Analisis Kadar Kreatinin pada Laki-Laki Pecandu Kopi di Dusun IV Desa Saentis - Qibetya, Ananda Nurul; Suharsih, Suharsih; Parinduri, Junaidi; Tamara, Chatrine Virginia (Mahesa Research Center, 2025)
Coffee consumption has become a part of people's lifestyles, especially among men. The main component of coffee is caffeine, which has a stimulating effect on the central nervous system. However, excessive consumption can lead to kidney function disorders, which can be identified through increased serum creatinine levels. This study aims to describe creatinine levels in male coffee addicts in Dusun IV, Saentis Village, Percut Sei Tuan District. This research employs a descriptive observational method with a cross-sectional approach. A total of 25 male coffee addicts had their serum creatinine levels measured using the enzymatic method with the Indiko Plus Analyzer. The results showed that the average creatinine level was 1.72 g/dL, with the lowest at 0.77 g/dL and the highest at 2.01 mg/dL. A total of 28% of respondents had high creatinine levels, while 72% were within the normal range. Respondents aged ≥35 years tended to have higher creatinine levels compared to those under 35 years old. Coffee consumption of ≥5 cups per day was associated with increased creatinine levels. This study indicates that excessive coffee consumption may pose a risk to kidney health.